Aterian shell beads from the coastal site of El Mnasra Cave (Rabat-Témara, Morocco): Specificities of the north African MSA personal ornaments - Emilie Campmas; Matthieu Lebon; Catherine Dupont; Manon Bondetti; Eslem Ben Arous; Arnaud Lenoble; Driss Chahid; Pierre Lozouet; Ludovic Bellot-Gurlet; Mohamed Abdeljalil El Hajraoui; Roland Nespoulet (PLoS ONE, 2026)
The use of Nassariidea shells as personal ornaments is attested to an increasing number of Middle Stone Age (MSA) archaeological sites in northern and southern Africa. The chronological extent of this behavior is constantly moving back in time; currently, the oldest evidence has been identified at the Bizmoune cave site in Morocco back to the MIS 6. Although these evidences make it possible to refine the spatial and temporal distribution of this behavior, shell beads remain rare in Middle Stone Age assemblages and are generally composed of several beads, or at best dozens, for each of these sites. This restricts our understanding of the behaviors specifically related to the collection, selection and preparation phases of shells, and potentially limits our understanding of their use. In this article, we studied shell beads from MSA layer US 8 from the coastal archaeological site of El Mnasra Cave (Rabat-Témara, Morocco). This collection corresponds to the largest MSA shell bead assemblage in Africa (272 Tritia cf . gibbosula, 6 Tritia corniculum and 3 Columbella rustica in US 8 with 154 of them showing smoothing of the perforation edge, facet of abrasion, or traces of pigment). The shell bead assemblage of El Mnasra presents features previously observed at other MSA sites, connecting it to a North African cultural context; however, the size of the El Mnasra shell bead assemblage, and the presence of shell sources near the site, allows us to identify specific features that could be related to particular modes of use as ornaments. These specific features include the prevalence of un-perforated shells, some of which show use-wear, that could have been fixed on items without having been perforated. These results provide new insights into the wide range of variants and originalities of shell bead uses over a relatively “short” chronological phase, between 115 and 94 ka and can be correlated with the multistep evolutionary scenario proposed for South Africa. The archaeological documentation presented here shows that El Mnasra Cave provides a significant contribution to the study of culturing the Palaeolithic body in North Africa.